The effect of the state of the intestinal microbiome on the performance of cyclical sports athletes according to ergometric testing indicators - Yu. I. Koryukalov; M. S. Lapshin; M. V. Kondashevskaya; A. S. Bakhareva; E. Yu. Savinih (Спортивная медицина: наука и практика)
Purpose: to assess the functional-metabolic state and intestinal microbiota of athletes of cyclic sports with high and low levels of performance.Materials and methods: the study involved 20 male athletes of cyclic sports aged 18–22 years. Based on the results of the athletes’ maximum performance — relative speed (Vrel.), shown in the ergometry test, the group was divided into two subgroups. To determine the presence or absence of intestinal dysbacteriosis, microbiological examination of feces was used.Results: High performance athletes (HPA) had significantly higher values of the circulatory efficiency coefficient (CEC) and aspartate aminotransferase (AST). In the HPA group, a positive correlation was found between the level of liver enzyme activity and intestinal microflora, as well as the activity of the ALT enzyme and speed characteristics. In the group of low performance athletes (LPA), positive correlations were found between performance indicators and hemolytic E. coli. Opportunistic bacteria were found in 40 % of men in the LPA group.Conclusion: In athletes with a high level of physical performance, the functional state was characterized by the activation of anabolic processes. Whereas in athletes with a low level of physical performance, catabolic processes prevailed, caused by the presence of opportunistic and pathogenic microorganisms in the intestine. It was concluded that athletes should regularly undergo ergometric testing with a study of the intestinal microbiome in order to prevent the development of dysbiosis.